The therapeutic potential of sialylated Fc domains of human IgG - Richard J. Pleass (Taylor & Francis Group, 2021)
Pathogens frequently use multivalent binding to sialic acid to infect cells or to modulate immunity through interactions with human sialic acid-binding immunoglobulin-type lectins (Siglecs). Molecules that interfere with these interactions could be of interest as diagnostics, anti-infectives or as immune modulators. This review describes the development of molecular scaffolds based on the crystallizable fragment (Fc) region of immunoglobulin (Ig) G that deliver high-avidity binding to innate immune receptors, including sialic acid-dependent receptors. The ways in which the sialylated Fc may be engineered as immune modulators that mimic the anti-inflammatory properties of intravenous polyclonal Ig or as blockers of sialic-acid-dependent infectivity by viruses are also discussed.